Towards Modeling False Memory With Computational Knowledge Bases. (21st December 2016) - Li, Justin; Kohanyi, Emma
Abstract: One challenge to creating realistic cognitive models of memory is the inability to account for the vast common–sense knowledge of human participants. Large computational knowledge bases such as WordNet and DBpedia may offer a solution to this problem but may pose other challenges. This paper explores some of these difficulties through a semantic network spreading activation model of the Deese–Roediger–McDermott false memory task. In three experiments, we show that these knowledge bases only capture a subset of human associations, while irrelevant information introduces noise and makes efficient modeling difficult. We conclude that the contents of these knowledge bases must be augmented and, more important, that the algorithms must be refined and optimized, before large knowledge bases can be widely used for cognitive modeling. Abstract : Li and Kohanyi examine how to incorporate large‐scale knowledge‐bases such as WordNet and DBPedia into a cognitive model of the Deese‐Roediger‐McDermott false memory task. They have lessons for other models using large databases as knowledge.